Views of Yahya Akyüz on Turkish Education History - Çam, Hüseyin (Bartin University, 2018)
Education is a life-long process that starts with the existence of human- being. Education is a field which all the societies and the thinkers of these societies have dealt with in a vital way from past to present. Societies are striving to build their future by owning their own history.When we examine the field of ideas, ideas, institutional development and practice in our education history, it is seen that there is a very important experience accumulation. As well as the positive and negative aspects of this accumulation, there are also aspects that are noteworthy or of little value. Considering our intellectual history, it can be seen that there are a large number of studies in this field. With years of experience and a great deal of accumulated knowled get hat has an important position among these, Yahya Akyüz's view point about education and his opinion regarding the Turkish National Education were studied.Yahya Akyüz’s studies were analyzed in an attempt to reveal his views and documentary scanning method was selected as a method for analyzing.The objective of this study is to reveal the opinions of our valuable scholar Yahya Akyüz about education and analyze their reflection on our education system today. By scanning Yahya Akyüz's Works and Works that were written about him, his opinions and thinges on education were found out.

Eğitim, insanoğlunun varlığıyla birlikte başlayan ve devam eden bir süreçtir. Eğitim, geçmişten günümüze kadar tüm toplumların ve bu toplumlardaki düşünürlerin, önemle ele aldıkları bir alandır. Toplumlar, kendi tarihlerine sahip çıkarak geleceğini inşa etme gayretini göstermektedir. Eğitim tarihimizde fikir, düşünce, kurumsal gelişme, uygulama alanı incelendiğinde çok önemli bir tecrübe birikimi olduğu görülmektedir. Bu birikimin olumlu ve olumsuz yönleri olduğu gibi, dikkate değer ya da pek değer taşımayan yönleri de bulunmaktadır. Düşünce tarihimize bakıldığında bu alanda çok sayıda çalışma olduğu görülmektedir. Bunlar içerisinde önemli bir yere sahip olan, yılların verdiği tecrübe ve bilgi birikimiyle Yahya Akyüz’ün eğitime bakışı ve Türk eğitim tarihini konu edinen düşüncesi araştırılmıştır. Yahya Akyüz’ün görüşlerinin ortaya çıkarılması amacıyla, eserleri incelenmiş ve araştırmada yöntem olarak belgesel tarama yöntemi seçilmiştir. Bu çalışmanın amacı değerli bir bilim adamı olan Yahya Akyüz’ün eğitim görüşlerini ortaya çıkarmak ve günümüz eğitim sisteminde yansımalarını araştırmaktır. Yahya Akyüz’ün eserleri ve hakkında yazılan eserler taranarak O’nun eğitim düşünceleri ve dayanak noktaları ortaya çıkarılmıştır.
Yahya Akyüz'ün Türk Eğitim Tarihine İlişkin Görüşleri
Keywords: Studies on Education; Eğitim Üzerine Çalışmalar